(untitled) (Journal Of Educational and Psychological Researches, 2018)
The study aims to analyze computer textbooks content for preparatory stage according to the logical thinking. The researcher followed the descriptive analytical research approach (content analysis), and adopted an explicit idea during the analysis process. One of the content analysis tools which was designed based on mental processes employed during logical thinking has utilized to figure out the study results. The findings revealed that logical thinking skills formed (52%) in fourth preparatory textbook and (47%) in fifth preparatory textbook.